A Disruptive Peace?: Economic Practices, Intrafamilial Relations, and the “Things that Make for Peace” according to Luke - Newberry, Julie (Modern theology, 2025)
Although some passages in Luke-Acts connect Jesus with peace (e.g., Luke 2:14; Acts 10:36), closer consideration of the Lukan peace motif yields a complex picture. This article contributes to our understanding of Lukan peace by examining two passages in which peace occurs alongside some of Jesus's harder words about financial disruption and intrafamilial division in the context of discipleship. I first analyze Luke 12:49-53, which includes Jesus's statement that he did not come to “give peace on the earth” (12:49) and describes households turned against themselves (12:52-53). Then, I take up Luke 14:25-33, which refers to peace within a parable about costly discipleship (14:32). Through attention to the Lukan narrative setting and Old Testament/Hebrew Bible intertexts, I show how these passages highlight the rather unpeaceful temporal effects that discipleship may have on financial stability and familial relationships. At the same time, Luke's Gospel also conveys the worthwhileness of enduring such disruptions for the sake of Jesus, who as the crucified and risen Lord offers both present and eschatological peace (e.g., 24:36). Without attempting to resolve all questions about Lukan peace, the interpretation advanced here brings into focus some practical theological invitations/challenges posed by Luke's nuanced treatment of this motif.